Liquid-like behaviours of metallic glassy nanoparticles at room temperature - C. R. Cao (Nature Portfolio, 2019)
Nanoscale materials often exhibit size-dependent behaviour. Here, the authors use electron microscopy to quantitatively study the size-related dynamics of amorphous metallic nanoparticles, finding that particles below a critical size are in a supercooled liquid state at room temperature, with a viscosity much lower than that of bulk glasses.